Presence of H3K4me3 on Paternally Expressed Genes of the Paternal Genome From Sperm to Implantation - Ishihara, Teruhito; Griffith, Oliver W.; Suzuki, Shunsuke; Renfree, Marilyn B. (Frontiers in Cell and Developmental Biology, 2022)
Genomic imprinting, parent-of-origin specific gene expression, is controlled by differential epigenetic status of the parental chromosomes. While DNA methylation and suppressive histone modifications established during gametogenesis suppress imprinted genes on the inactive allele, how and when the expressed allele gains its active status is not clear. In this study, we asked whether the active histone-3 lysine-4 trimethylation (H3K4me3) marks remain at paternally expressed genes (PEGs) in sperm and embryos before and after fertilisation using published data. Here we show that mouse sperm had the active H3K4me3 at more than half of known PEGs and these genes were present even after fertilisation. Using reciprocal cross data, we identified 13 new transient PEGs during zygotic genome activation. Next, we confirmed that the 12 out of the 13 new transient PEGs were associated with the paternal H3K4me3 in sperm. 9 out of the 12 genes associated with the paternal H3K4me3 in zygotes. Our results show that paternal H3K4me3 marks escape inactivation during the histone-to-protamine transition that occurs during sperm maturation and are present in embryos from early zygotic stages up to implantation.